A study on fire protection system for historical school building / Anas Firdaus Rahmat - Rahmat, Anas Firdaus (2008)
Lost of life and property by fire most commonly occur because of ignorance about the nature of fire and its behavior, possibly lethal, in circumstances that normally appear perfectly harmless. If a successful campaign is to be conducted against fire and its dreadful consequences then the adversary must be fully understood. Never forget, prevention is better than cure. Fire spread is very quickly. Fire tends to double its size at regular intervals, sometimes as quickly as within minutes. Fires in buildings develop differently to fires in the outdoors, and the speed at which they spread takes most people completely by surprise. It is said that the average domestic room with usual equipment will be totally alight in about four minutes. Often, members of the public fail to comprehend the speed at which fires develop and do not believe that they have to evacuate or do anything in relation to their safety.